Beyond primary care: reorganization of SUS through the intersection of the political and economic sectors - Göttems, Leila Bernardo Donato; Pires, Maria Raquel Gomes Maia (Saúde e Sociedade, 2009)
The limits and possibilities concerning the restructuring of the health services of Sistema Único de Saúde (SUS - National Health System) are discussed based on primary care. The hypothesis is that primary care, which means integrated action of promotion, prevention and recuperation of the population's health, despite the fact that it is a political space for the production of knowledge and of power-sharing technology, it has little influence on the reorganization of the health market in Brazil, which negatively affects its potential concerning the inversion of the primary care model. This paper aims to contextualize primary care in the health assistance management of SUS, and to think theoretically about the reorganization of the SUS services starting from primary health care, and taking into account the economic dimensions of the social policies. The theoretical and documental research had a qualitative approach. Critical analysis of official documents, both national and international, was performed. The conclusion is for the need of a primary care that is better articulated with the medium and high complexities, able to interfere in the logic of the offer based on the demand and to reduce inequities.